Prevalence and Risk Factors of Developing Fistula or Organ Perforation in Patients Treated with Lenvatinib for Radioiodine-Refractory Thyroid Cancer. Issue 5 (23rd July 2021) - Valerio, Laura; Giani, Carlotta; Agate, Laura; Molinaro, Eleonora; Viola, David; Bottici, Valeria; Matrone, Antonio; Puleo, Luciana; Lorusso, Loredana; Cappagli, Virginia; Ribechini, Alessandro; Elisei, Rossella
Abstract : Introduction: Tyrosine kinase inhibitors represent a better treatment in patients with radioiodine-refractory differentiated thyroid cancer (RAI-R DTC). Lenvatinib is usually well-tolerated, but sometimes, it is associated with serious and even life-threatening side effects. The aim of this study was to evaluate the prevalence of and the potential risk factors for fistula and/or organ perforation in RAI-R DTC patients treated with lenvatinib. Methods: This study included data from advanced and progressive RAI-R DTC patients treated with lenvatinib from February 2011 to February 2020 who were followed up at a single center. The clinical-pathological features and the biochemical and morphological results of the patients were collected at the time of starting lenvatinib and during the follow-up. Results: Fourteen of 95 (14.7%) locally advanced or metastatic RAI-R DTC patients treated with lenvatinib developed a fistula or organ perforation. Nine of 14 (64.3%) patients had tumor infiltration of the trachea, bronchus, esophagus, pleura, or bladder. Five of 14 (35.7%) had a bowel perforation, but only 2 had preexisting diverticulosis. Evaluation of the risk factors for developing a fistula or organ perforation showed that the presence of tumor infiltration and the tumor histology (papillary and poorly differentiated vs. follicular and Hurthle thyroid cancer) were significantly correlated with the development of a fistula or organ perforation ( p = 0.003 and p = 0.02, respectively). In the subgroup of patients with tumor infiltration, we found that the papillary thyroid cancer histotype was the only potential predictor of fistula development. External beam radiation therapy (EBRT), the starting dose of lenvatinib, and the duration of treatment were not relevant for the development of fistula. Conclusions: In metastatic thyroid cancer patients treated with lenvatinib, the presence of tumor infiltration and histological type should be considered as potential risk factors for the development of fistula or organ perforation, although they do not represent an absolute contraindication. Although EBRT and the presence of diverticulosis were not significantly associated with the development of fistula and organ perforation, they should be regarded as potential additional reasons for the development of these complications. According to our findings, there is no reason to start lenvatinib at a lower daily dose when tumor infiltration is present.